PENGEMBANGAN DAN PEMANFAATAN MEDIA VIDEO INSTRUKSIONAL UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Ismaniati, Christina (MAJALAH ILMIAH PEMBELAJARAN, 2018)
Abstract One of the many problems faced by education in Indonesia is the low quality. Several attempts have been taken by the government to resolve the issue, but the results is still far from expectations. Based on expert opinion, the problem of low quality education should be focused on improving the quality of learning, by developing and using instructional media or learning resources that is available in the learning environment. Learning video is an qfective medium to be used to facilitate student’s learning and it suites to serve students of auditory and visual learning type. Therefore, to improve the learning process quality, teachers are not only expected to make use of media and learning resources that are available but also to develop the learning media, especially learning video